2010
DOI: 10.1080/02701367.2010.10599629
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Functional Classification Levels and Anaerobic Performance of Wheelchair Basketball Athletes

Abstract: Wheelchair basketball athletes are classified using the International Wheelchair Basketball Federation (IWBF) functional classification system. The purpose of this study was to evaluate the relationship between upper extremity anaerobic performance (AnP) and all functional classification levels in wheelchair basketball. Ninety-seven male athletes from the Polish and Lithuanian national wheelchair basketball leagues took part in this study. The Wingate Anaerobic Test was used to assess four AnP indexes with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 9 publications
6
47
0
12
Order By: Relevance
“…The anaerobic capacity of athletes with disabilities has often been the subject of scientific research over the years [8][9][10][11][12][13][14][15][16][17]. The selection of a homogenous group (different types of disabilities and sports for the disabled) as well as small sample size are crucial problems regarding the standardisation of results and the definition of standards for anaerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The anaerobic capacity of athletes with disabilities has often been the subject of scientific research over the years [8][9][10][11][12][13][14][15][16][17]. The selection of a homogenous group (different types of disabilities and sports for the disabled) as well as small sample size are crucial problems regarding the standardisation of results and the definition of standards for anaerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies related to anaerobic capacity were conducted on wheelchair rugby and basketball players as well as para-canoeists. They revealed that athletes with the most limited functional capacities (the highest disability level) differed from others in terms of anaerobic parameters [8,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations